A new genus and species of clearwing moth (Lepidoptera: Sesiidae) from Ethiopia - Gorbunov, Oleg G. (Zootaxa, 2018)
A new genus and species from the tribe Synanthedonini (Lepidoptera, Sesiidae) is described and illustrated from Ethiopia: Jerbeia darkovi gen. et sp. nov. The new genus differs from the all known Afrotropical sesiid genera in the combination of the following characters: parallel veins R1–R3 of the forewing, the valva of the male genitalia with a ventral crista and the vesica is armed with flat dentate cornuti. The type series, which consists of 12 males, was collected with the help of artificial sex attractants. The female and the larval bionomics are unknown.